Is a national time target for emergency department stay associated with changes in the quality of care for acute asthma? A multicentre pre‐intervention post‐intervention study. (13th January 2016) - Jones, Peter; Wells, Susan; Harper, Alana; LeFevre, James; Stewart, Joanna; Curtis, Elana; Reid, Papaarangi; Ameratunga, Shanthi
Abstract: Objective: There is debate whether targets for ED length of stay introduced to reduce ED overcrowding are helpful or harmful, as focus on a process target may divert attention from clinical care. Our objective was to investigate the effect of a national ED target in Aotearoa New Zealand on the recommended care for acute asthma as this is known to suffer in overcrowded departments. Methods: We conducted a retrospective chart review study across four sites from 2006 to 2012 (target introduced mid 2009). The primary outcome was time to steroids in the ED. The secondary outcomes were other aspects of asthma care in ED. We used general linear models or logistic regression as appropriate to assess care before and after the target. Results: Among the 570 (of 1270 randomly selected cases) eligible for analysis, no difference was demonstrated in time to steroids: least square mean (95% CI) = 58.1 (49–67.5) min before and 50.4 (42.9–55.8) min after the target ( P = 0.15). More patients received steroids in ED after the target, OR (95% CI) = 2.1 (1.2–4.3). No differences were demonstrated in those receiving steroid prescriptions or re‐presentations: OR (95% CI) = 1.3 (0.9–1.96) and 1.1 (0.5–2.3), respectively. Changes in pre‐target and post‐target ED and hospital length of stay varied between hospitals. Conclusion: Introduction of the target was not associated with a change in times to steroids in ED, although more patients received steroids in ED indicating closer adherence to recommended practice.